The two-headed Russian eagle, European partner or outsider? - Lenzi, Guido (Rivista di studi politici internazionali, 2011)
with the Eu additional to the ’reset’ of its bilateral relations with the Usa. A more meaningful partnership between Brussels and Moscow would be conducive to the stabilization of the ‘common contiguity belt’ and contribute to a pan-European ‘common law’, that could also constitute a model for the reintegration of the international system. To this end, information and consultation mechanisms would prove more effective than the legally binding new security architecture put forth by Pres. Medvedev. An endeavor more akin to organic gardening than to solid stone constructions. Pour rétablir son role de protagoniste mondial, la Russie devrait diversifier sa politique étrangère, et accepter un partenariat stratégique avec l’Union européenne en complement du ‘reset’ de ses rapports avec les États Unis. Un rapport plus constructif entre Bruxelles et Moscou pourrait conduire à la stabilization de leur ‘ceinture commune de contiguité’ et contribuer à l’instauration d’un ‘droit commun’ pan-européeen, et constituer aussi un modèle pour la réintegration du système international dans son ensemble. Dans ce sens, des méchanismes d’information et de consultation seraient plus efficaces que la nouvelle architecture de sécurité juridiquement contraignante proposée par le Prés. Medvedev. Une oeuvre qui s’apparente au jardinage plutòt qu’à la construction de bâtiments. Key words: New European Security Strategy; Eu-Russia relationship; European common law; Pan-European stabilization; Russian foreign policy.